Synergizing Multigrid Algorithms with Vision Transformer: A Novel Approach to Enhance the Seismic Foundation Model - Wu, Huiwen; Zhang, Shuo; Liu, Yi; Ye, Hongbin (Proceedings of the AAAI Conference on Artificial Intelligence, 2026)
Due to the rapid advancement and homogenization of Artificial Intelligence (AI) technology development, transformer-based foundation models have revolutionized scientific applications, such as drug discovery, materials research, and astronomy. However, seismic data presents unique characteristics that require specialized processing techniques for pretraining foundation models in seismic contexts with high- and low-frequency features playing crucial roles. Existing Vision Transformer (ViT) with sequential image tokenization fails to efficiently and effectively capture both high- and low-frequency seismic information because they ignore the intrinsic structural patterns of seismograms. This work introduces ADATG, a novel adaptive two-grid training strategy with Hilbert encoding, explicitly tailored for seismogram data and leveraging the hierarchical structures inherent in seismic data. Specifically, our approach employs spectrum decomposition to separate high- and low-frequency components, and hierarchical Hilbert encoding to represent the data effectively. Moreover, inspired by the frequency principle, we propose an adaptive training strategy that initially emphasizes coarse-level information and then progressively refines the model’s focus on fine-level features. Extensive experiments demonstrate the effectiveness and efficiency of our method. This research highlights the importance of data encoding and training strategies informed by the distinct characteristics of high- and low-frequency features in seismic images, ultimately enhancing the pretraining of visual seismic foundation models.